Clonal hematopoiesis of indeterminate potential is rare in pediatric patients undergoing autologous stem cell transplantation - Kartal-Kaess, Mutlu; Karow, Axel; Bacher, Ulrike; Pabst, Thomas; Joncourt, Raphael; Zweier, Christiane; Kuehni, Claudia E.; Porret, Naomi Azur; Roessler, Jochen (Pediatric Hematology and Oncology, 2024)
Clonal hematopoiesis of indeterminate potential (CHIP) describes recurrent somatic gene mutations in the blood of healthy individuals, associated with higher risk for hematological malignancies and higher all-cause mortality by cardiovascular disease. CHIP increases with age and is more common in adult patients after chemotherapy or radiation for cancer. Furthermore, in some adult patients undergoing autologous stem cell transplantation (ASCT) or thereafter, CHIP has been identified. In children and adolescents, it remains unclear how cellular stressors such as cytotoxic therapy influence the incidence and expansion of CHIP. We conducted a retrospective study on 33 pediatric patients mostly with solid tumors undergoing ASCT for presence of CHIP. We analyzed CD34+ selected peripheral blood stem cell grafts after several cycles of chemotherapy, prior to cell infusion, by next-generation sequencing including 18 “CHIP-genes”. Apart from a somatic variant in TP53 in one patient no other variants indicative of CHIP were identified. As a CHIP-unrelated finding, germline variants in CHEK2 and in ATM were identified in two and four patients, respectively. In conclusion, we could not detect “typical” CHIP variants in our cohort of pediatric cancer patients undergoing ASCT. However, more studies with larger patient numbers are necessary to assess if chemotherapy in the pediatric setting contributes to an increased CHIP incidence and at what time point.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Autologous stem cell transplantation; cancer; CHIP; pediatric